2012
DOI: 10.5923/j.plant.20120204.01
|View full text |Cite
|
Sign up to set email alerts
|

<i>In Vitro</i> Mutation Induction and Selection of Chrysanthemum (<i>Dendranthema Grandiflora</i> Tzelev) Lines with Improved Resistance to <i>Septoria Obesa</i> Syd

Abstract: This paper describes in vitro mutation selection technique for improved resistance in chrysanthemum (Dendranthema grandiflora Tzelev) cv. Snow Ball against culture filtrate of Septoria obesa, a leaf spot pathogen. The callus was initiated fro m leaf exp lant on MS med iu m supplemented with 10 mg/ l kinetin and 1 mg/l NAA. Opt imal doses of gamma radiation and culture filtrate on the per cent survival of calli were standardized. The optimal dose of gamma radiation was 20 Gy and that of culture filtrate was 15%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 17 publications
0
5
0
3
Order By: Relevance
“…Development of red rot (Colletotrichum falcatum) resistant sugarcane (Saccharum officianarum) by induced mutation was reported by Ali et al (2007). Similarly, chrysanthemum plants resistant to Septoria obesa were obtained by Kumar et al (2012) after gamma irradiation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Development of red rot (Colletotrichum falcatum) resistant sugarcane (Saccharum officianarum) by induced mutation was reported by Ali et al (2007). Similarly, chrysanthemum plants resistant to Septoria obesa were obtained by Kumar et al (2012) after gamma irradiation.…”
Section: Discussionmentioning
confidence: 99%
“…'Snow Ball' after gamma irradiation. Studies conducted by Badr et al (2006) and Kumar et al (2012) indicated that RAPD markers can be used effectively for genetic diversity studies among radio-mutants. Similarly, occurrence of polymorphism was reported by Minisi et al (2013) in gamma irradiated seeds of Molucella laevis.…”
Section: Discussionmentioning
confidence: 99%
“…Planlet Fiji Kuning masih vigor dari dosis 15, 20, 25, 30, hingga perlakuan dosis 35 Gy. Sementara itu, semua perlakuan dosis sinar gamma (15,20,25,30,35,40, dan 45 Gy) pada planlet varietas Sunny masih berwarna hijau dan vigor. Sebaliknya, pada kalus varietas Jimla, hanya perlakuan dosis 5 Gy yang tampak masih vigor dan berwarna hijau kekuningan.…”
Section: Jumlah Planlet Vigor Pascairadiasiunclassified
“…Gamma-ray irradiation has advantages over treatment with chemical mutagens such as ethyl methane sulfonate (EMS) in that it induces DNA damage relatively randomly, resulting in various types of mutations including point mutations, indels, and chromosome aberrations (Tanaka et al, 2010). Therefore, gamma-ray irradiation has been the main treatment used in various plants, particularly ornamental plants such as orchids (Kikuchi, 2000), Anthurium (Puchooa, 2005), chrysanthemum (Kumar et al, 2012;Yamaguchi et al, 2008), and Paphiopedilum (Luan et al, 2012), for over 80 years. Recently, irradiation with ion beams, which are different from gamma-ray in that they are generated by accelerators and has specific mass and charge according to types of ions, has been proven to be very effective in mutation breeding in terms of biological effectiveness, mutation frequency, and range of mutation spectrum compared with gamma ray (Hase et al, 2012).…”
Section: Introductionmentioning
confidence: 99%